FORMATION OF LOCAL BUDGETS OF TERRITORIAL COMMUNITIES IN THE CONTEXT OF RUSSIA'S FULL-SCALE INVASION - SYNCHAK, Viktor; SUPIVSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The topic of this publication is particularly relevant, as research into the process of local budget formation in wartime allows us to assess the capacity of communities to achieve financial independence and to develop key measures to ensure the financial stability of local government budgets. It has been established that the formation of local budgets in Ukraine has undergone significant changes in the context of Russia's full-scale invasion. The main problems were a decline in local budget revenues due to a decline in economic activity, reduced employment, and population outflow. At the same time, expenditures on humanitarian needs, social protection, ensuring the functioning of critical infrastructure, and supporting internally displaced persons have increased significantly. The study showed that communities that were able to adapt to new conditions proved to be more successful. The ability to respond quickly to change became particularly important. It has been proven that the success of local community budgeting in wartime largely depends on the interaction between local authorities, businesses, and civil society. Therefore, local budgeting requires the implementation of appropriate measures both during wartime and in post-war reconstruction. Such measures include: creating conditions at the state level to support local economic development; expanding the fiscal powers of starosts in starost districts through legislation regarding their participation in the formation of local community budget revenues; improving digital tools for managing local budgets; and strengthening the tripartite partnership between local authorities, business, and civil society.
Keywords: local budgets of territorial communities; formation of local budgets; local taxes and fees; harmonization of the budget system of Ukraine; implementation of local budgets; screening of domestic legislation; European integration processes; coordination of financial management procedures in territorial communities; financial decentralization; special fund of the state budget; general fund of local budgets; financially autonomous local budgets; dispersion of the tax base; taxpayer accounting; support for local economic development; management of local budgets